Strategi Pemasaran Digital Busana Muslim di saat Pandemi Covid 19 - Hasna Aulia; Indri Rachmawati (Bandung Conference Series: Communication Management, 2022)
Abstract. The times have made marketing more sophisticated so that the emergence of digital marketing through e-commerce is one of them Shopee. Elzatta has joined Shopee for 5 years, from the assessment and appearance on e-commerce Shopee Elzatta is more attractive than other brands. This research was conducted so that the discussion focused on how digital marketing through e-commerce Shopee Elzatta during the covid-19 pandemic in maintaining sales and promoting products. The purpose of this research is to find out Elzatta uses digital marketing through Shopee e-commerce, to find out Elzatta's obstacles that occur in promoting products through Shopee e-commerce during the covid-19 pandemic, and to find out Elzatta's strategy in promoting products through e-commerce. Shopee during the covid-19 pandemic. In this study, the researcher uses the constructivist paradigm and uses a qualitative method with a case study approach. The technique of collecting data in this research is by observation and interviews. Informants in this study were Sales digital marketing Elzatta and Admin Shopee Elzatta. The data validity test in this study was source triangulation because it involved two informants. The results of this study are Elzatta uses Shopee e-commerce as a medium to carry out digital marketing activities because Shopee e-commerce is the platform most widely used by the public for online shopping which features free shipping, discounts and so on. Elzatta has experienced obstacles in promoting its products, due to the implementation of restrictions on community activities which are commonly called (ppkm) with digital marketing through Shopee e-commerce experiencing quite an increase. The strategy carried out in digital marketing through Shopee Elzatta's e-commerce during the covid-19 pandemic is through preparation, planning, implementation, and evaluation. Elzatta also participates in promotional programs at Shopee such as monthly sales and uses ads, and there are also special products so that can increase traffic and good exposure. The solution taken by Elzatta in promoting digital marketing through Shopee e-commerce during the covid-19 pandemic is by participating in the Shopee promotion program and also because now it's PPKM so Elzatta is doing a PPKM promotion, the purpose of Elzatta's PPKM promotional program is "delivery promotion. Pride cheap "and free postage. Abstrak. Perkembangan zaman membuat pemasaran semakin canggih sehingga munculnya digital marketing melalui e-commerce salah satunya Shopee. Elzatta bergabung di Shopee sudah 5 tahun, dari penilaian dan penampilan di e-commerce Shopee Elzatta lebih menarik dibanding brand lainnya. Penelitian ini dilakukan agar terfokusnya pembahasan mengenai bagaimana digital marketing melalui e-commerce Shopee Elzatta saat pandemi covid-19 dalam mempertahakan penjualan dan mempromosikan produk. Tujuan dari penelitian ini adalah untuk mengetahui Elzatta menggunakan digital marketing melalui e-commerce Shopee, untuk mengetahui hambatan Elzatta yang terjadi dalam mempromosikan produk melalui e-commerce Shopee di saat pandemi covid-19, serta untuk mengetahui Strategi Elzatta dalam mempromosikan produk melalui e-commerce Shopee di saat pandemi covid-19. Dalam penelitian ini peneliti menggunakan Paradigma konstruktivis serta menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data pada penelitian ini adalah dengan observasi dan wawancara. Informan dalam penelitian ini adalah Sales digital marketing Elzatta dan Admin Shopee Elzatta. Uji keabsahan data pada penelitian ini adalah triangulasi sumber karena melibatkan dua informan. Hasil dari penelitian ini adalah Elzatta menggunakan e-commerce Shopee sebagai media untuk melakukan kegiatan pemasaran digital karena e-commerce Shopee merupakan platform yang paling banyak digunakan oleh masyarakat untuk belanja online yang memiliki fitur gratis ongkir, diskon dan sebagainya. Elzatta mengalami hambatan dalam mempromosikan produknya, dikarenakan adanya pemberlakuan pembasatan kegiatan masyarakat yang biasa di bilang (ppkm) dengan adanya pemasaran digital melalui e-commerce Shopee mengalami cukup peningkatan. Strategi yang dilakukan dalam digital marketing melalui e-commerce Shopee Elzatta saat pandemi covid-19 yaitu melalui persiapan, perencanaan, pelaksanaan, dan evaluasi Elzatta juga mengikuti program promosi di shopee seperti sale di tiap bulannya dan menggunakan iklan ads, dan juga ada produk khusus sehingga bisa meningkatkan traffic dan exposure yang baik. Solusi yang ditempuh oleh Elzatta dalam mempromosikan digital marketing melalui e-commerce Shopee saat pandemi covid-19 yaitu dengan cara mengikuti program promosi Shopee dan juga karena sekarang sedang ppkm jadi Elzatta melakukan promosi ppkm, maksud dari program promosi ppkm Elzatta itu “promo pengiriman kebangetan murahnya” dan gratis ongkir.